Recent increases in Arctic freshwater flux affects Labrador Sea convection and Atlantic overturning circulation - Qian Yang; Timothy H. Dixon; Paul G. Myers; Jennifer Bonin; Don Chambers; M. R. van den Broeke; Mads H. Ribergaard; John Mortensen (Nature Communications, 2016)
Labrador Sea convection and the Atlantic overturning circulation are sensitive to surface freshening of the North Atlantic. Here, the authors show that the recent increases in Arctic freshwater flux can directly weaken Labrador Sea convection and potentially affect the overturning circulation.